Сучасний стан та перспектива селекції генофондного стада лебединської породи - Салогуб, А.М.; Хмельничий, Л.М. (Фактори експериментальної еволюції організмів, 2013)
Aims. In the aspect of maintainance of genofond herd of cows of lebedinskoy breed the studied is deep the high-quality signs of milk are hereditarily predefined in their connection with maintenance of fat in the dynamics of lactations. Methods. Research was conducted in a pedigree factory from breeding of lebedinskoy breed. The basic physical and chemical indexes of milk determined the method of infra-red diagnostics on the automatic analyzer of quality of milk of «Laktoscope» of firm «Deltainstruments» (Holland). Results. The sufficient level of yield is set for the taken into account lactations, that confirms the competitiveness of cows of lebedinskoy breed. The level of changeability of maintenance of fat and albumen in milk satisfies the requirements of standard of breed, however testifies to the necessity of increase last, as maintenance of albumen for 20 years substantially went (on 0,2 % in comparing to his minimum value from literary data) down and needs plant-breeding improvement on a prospect through application of the rationally grounded of intrapopulation selection. Conclusions. The substantial decline of protein, is set in course of time in milk of cows of lebedinskoy breed certifies the necessity of careful selection of bulls-producers with a high pedigree value after proteinmilk. The account of the set directed connecting changeability between the signs of the suckling productivity will allow to promote efficiency of selection after them.